Differential effects of foraging strategies on carotenoid-derived plumage color and individual quality in stripe-tailed yellow finches - de-Carvalho, Mariana; Diniz, Pedro [UNESP]; Pires Júnior, Osmindo R.; Macedo, Regina H.; Nardoto, Gabriela B. (Wiley, 2025)
Carotenoid-based plumage color is crucial in avian mate selection, often serving as an indicator of individual quality. To determine whether carotenoid-derived color can be a sign of individual condition and if there is a relationship between an individual's condition and color production, it is necessary to identify how carotenoids are acquired by individuals and subsequently used by the organism. Our objective was to determine how carotenoid pigments are used in the stripe-tailed yellow finch Sicalis citrina, a species wherein females exhibit a light yellowish ventral color while males are bright yellow. By using carbon and nitrogen stable isotope analyses we were able to determine if these carotenoid-derived colors are a signal of individual condition in terms of physiological stress and body condition. Females with low δ13C values (≈ −18‰) indicating the consumption of C3 and C4 seeds, exhibited colors shifted toward longer wavelengths and better body condition, and those with such color shifts also had higher carotenoid concentrations. In contrast, brighter females had higher δ15N values, indicating greater consumption of arthropods. Males with more saturated ventral patches had higher carotenoid concentrations, while those with colors shifted toward shorter wavelengths or lower H/L ratios, i.e. less stress, exhibited high δ15N values, suggesting that they supplement their diet with arthropods (δ15N ≈ 5‰). Our results show that the carotenoids dynamics in stripe-tailed yellow finches differ between sexes and highlight how food sources impact condition, stress, and ornamentation. Our study indicates that sexual dimorphism extends beyond plumage color to deeper physiological and ecological differences.
Keywords: carbon isotope; diet; lutein; nitrogen isotope; sexes; stable isotopes